Air Transport Area as an Object of State Regulation - O. V. Brusakova (Law and Safety)
It is emphasized that the aviation area is a high-tech sector of the economy of any state, the dynamic development of which requires streamlining national legislation in this area, expanding international cooperation, updating legal instruments used by public authorities in state regulation in the air transport area. In this regard, it is emphasized that the efficiency of the air transport area directly depends on the status of state regulation of aviation activities.